Synthesis of Implementations for Divide-and-Conquer Specifications - Bortin, Maksym (Anais do Simpósio Brasileiro de Métodos Formais (SBMF); 2022: Anais do XXV Simpósio Brasileiro de Métodos Formais, 2022)
The paper presents a systematic approach to the derivation of implementations from abstract specifications featuring a few structural properties. The method is applied in a case study concerning weighted finite matroids and the algorithmic construction of their optimal bases.